1996
DOI: 10.1007/bf00222955
|View full text |Cite
|
Sign up to set email alerts
|

Association of RFLP markers with loci conferring broad-based resistance to the soybean cyst nematode (Heterodera glycines)

Abstract: Soybean cyst nematode (SCN) is a major soybean yield-limiting pest. The present study was conducted to map broad-based SCN resistance loci from the cultivar 'Hartwig'. Two-hundred F2∶3 lines derived from the cross 'Williams 82' x 'Hartwig' were screened with a fourth-generation SCN inbred and 56 polymorphic molecular markers. Allele states and phenotypes were analyzed using stepwise regression and the model selection was made at P [Symbol: see text] 0.01. Four unlinked RFLP markers (A006, A567, A487, A112) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 20 publications
1
35
0
1
Order By: Relevance
“…Yue et al (2001aYue et al ( , 2001b reported that the interval between A006-Satt583 and Satt583-Sat_123 on LG B1 was associated with alleles conferring a resistance to the SCN races 1, 2 and 5. The RFLP marker A006 also related to resistance to SCN race 3 was reported by Vierling et al (1996). Since these regions overlap rhg-t2, some loci might be shared for resistance to different races.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Yue et al (2001aYue et al ( , 2001b reported that the interval between A006-Satt583 and Satt583-Sat_123 on LG B1 was associated with alleles conferring a resistance to the SCN races 1, 2 and 5. The RFLP marker A006 also related to resistance to SCN race 3 was reported by Vierling et al (1996). Since these regions overlap rhg-t2, some loci might be shared for resistance to different races.…”
Section: Discussionmentioning
confidence: 75%
“…and cyst-99 assays, respectively. Vierling et al (1996) reported the presence of an RFLP marker A567 associated with minor resistance to SCN race 3. Webb et al (2003) also detected a QTL for resistance to SCN races 1, 2, 5, 14 in the same region.…”
Section: Discussionmentioning
confidence: 99%
“…Locations included linkage group (LG) B1, mid Lg G and Lg B2 (chromosomes 11, 18 and 14;Vierling et al 1996;Wang et al 2001;Yue et al 2001). The findings suggest the existence of functional paralogs of Rhg1/Rfs2 among the duplicated regions of the soybean genome.…”
Section: Discussionmentioning
confidence: 86%
“…Hartwig derives from the cross between Forrest x PI 437654 genotypes and appears to have retained most of the SCN resistance of PI 437654 genotypes (Vierling et al, 1996). The F 2 plants obtained from five F 1 plants were selfed until the F 6 generation by the single seed descent (SSD) method (Brim, 1966).…”
Section: Methodsmentioning
confidence: 99%